Estimation of CO2 emissions that create tax collection in Costa Rica - Miranda Núñez, David (2023)
It seeks to estimate the contribution of the productive sectors and households with the generation of GHG emissions in Costa Rica and at the same time determine the relationship between the creation of jobs and added value with the generation of CO2 emissions by sector. The analysis involves tax collection through the payment of the tax on fuels, using the methodology of the Input Product Model with environmental expansion considering the 2017 MIP. Indicators are constructed that show the dependence of the productive sectors and households with respect to the use and consumption of hydrocarbons. The analytical exercise makes it possible to warn about the need to reorient production and households towards more eco-efficient processes that favor the creation of added value and a clean source of employment.